ERIC recommendations on TP53 mutation analysis in chronic lymphocytic leukemia - Pospíšilová, Šárka; Zenz, Thorsten (Leukemia, 2012)
Recent evidence suggests that - in addition to 17p deletion - TP53 mutation is an independent prognostic factor in chronic lymphocytic leukemia (CLL). Data from retrospective analyses and prospective clinical trials show that ∼5% of untreated CLL patients with treatment indication have a TP53 mutation in the absence of 17p deletion. These patients have a poor response and reduced progression-free survival and overall survival with standard treatment approaches. These data suggest that TP53 mutation testing warrants integration into current diagnostic work up of patients with CLL. There are a number of assays to detect TP53 mutations, which have respective advantages and shortcomings. Direct Sanger sequencing of exons 4-9 can be recommended as a suitable test to identify TP53 mutations for centers with limited experience with alternative screening methods. Recommendations are provided on standard operating procedures, quality control, reporting and interpretation. Patients with treatment indications should be investigated for TP53 mutations in addition to the work-up recommended by the International workshop on CLL guidelines. Patients with TP53 mutation may be considered for allogeneic stem cell transplantation in first remission. Alemtuzumab-based regimens can yield a substantial proportion of complete responses, although of short duration. Ideally, patients should be treated within clinical trials exploring new therapeutic agents.
Gesehen am 04.09.2018